Singapore and Food Security - Ong, Keng Yong (2017)
Food security can be enhanced by strategic initiatives. Land scarce countries can still do much for agriculture and farming with effective policy measures. Singapore has learned to address the multi-faceted challenges of food security with good planning, efficient utilisation of available resources and clear vision for the future.